2018
DOI: 10.1530/jme-17-0142
|View full text |Cite
|
Sign up to set email alerts
|

Role of upstream stimulatory factor 2 in glutamate dehydrogenase gene transcription

Abstract: Glutamate dehydrogenase (Gdh) plays a central role in ammonia detoxification by catalysing reversible oxidative deamination of l-glutamate into α-ketoglutarate using NAD or NADP as cofactor. To gain insight into transcriptional regulation of , the gene that codes for Gdh, we isolated and characterised the 5' flanking region of from gilthead sea bream (). In addition, tissue distribution, the effect of starvation as well as short- and long-term refeeding on Gdh mRNA levels in the liver of were also addressed. 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Glutamate dehydrogenase (GDH) reversibly catalases the oxidative deamination of glutamate to produce α-ketoglutarate (as an energy substrate for the Krebbs cycle) and ammonia, playing a key role in nitrogen excretion in fish [ 51 ]. The lower GDH activity ( Figure 3 A: 16) (and mean urea levels ( Figure 3 B: 12)) in the weight-loss groups indicates limited protein catabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Glutamate dehydrogenase (GDH) reversibly catalases the oxidative deamination of glutamate to produce α-ketoglutarate (as an energy substrate for the Krebbs cycle) and ammonia, playing a key role in nitrogen excretion in fish [ 51 ]. The lower GDH activity ( Figure 3 A: 16) (and mean urea levels ( Figure 3 B: 12)) in the weight-loss groups indicates limited protein catabolism.…”
Section: Resultsmentioning
confidence: 99%
“…However, promoter is a rough and ambiguous region relative to the TSS of a gene. Although long genomic fragments were defined as putative promoter regions in studies [ 21 , 22 ], the functional domains confirmed by experiment or selected for experiment were usually close to the TSSs [ 34 36 ]. Such phenomenon was also consistent with our finding in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, optimal growth of fish requires high levels of dietary protein, and amino acids are the most potent insulin secretagogues in fish (34). Therefore, transdeamination, which involves transferring of amino groups from amino acids to ␣-ketoglutarate to produce glutamate and subsequent glutamate deamination by GDH, is very important in the fish liver for entering the carbon skeleton of amino acids into the TCA cycle to obtain energy and for biosynthetic purposes (7,14,20,22,38). The fact that metformin markedly decreased GDH expression, and to a lesser extent ALT activity, suggests reduced amino acid deamination and transamination capacity in the liver of S. aurata, and, therefore, limited use of amino acids for gluconeogenic purposes, which, in turn, may be essential for the long-term hypoglycemic effect of metformin in the liver of S. aurata.…”
Section: Discussionmentioning
confidence: 99%